Body Size and Nutritional Status of Children Aged 6-12 Years in Jungkat Village, Jongkat District, Mempawah Regency - Candramila, Wolly; Bilqis, Khofifah Azmi; Mardiyyaningsih, Asriah Nurdini; Kurniati, Yulia; Suvani, Monika Susi; Hartini, Titin; Rohmatullayaly, Eneng Nunuz; Kawulur, Elda Irma Jeanne Joice (Bogor Agricultural University, Indonesia, 2025)
The significant impact of stunting in early childhood affects both physical growth and cognitive development. The prevalence of stunting in Jungkat Village highlights the importance of monitoring growth and development during mid-childhood (ages 6-12), as it is a critical period for cognitive, social, and physical development. The study aims to provide insights into the effectiveness of interventions in addressing stunting by describing the body size and nutritional status of children aged 6-12 in Jungkat Village. A cross-sectional method was employed in four primary schools in Jongkat District. Anthropometric measurements of body height and body weight were used to calculate nutritional status indices, including the body height-to-age index and body mass index. In Jungkat Village, children aged 6-12 show varied growth patterns, including high rates of stunting and obesity, with some stunted children maintaining normal BMI for age, indicating complex interactions between nutrition and growth. In addition, there is no significant sexual dimorphism in growth patterns at this age, but differences in weight are evident, with boys generally heavier after age 7. Environmental, socioeconomic, and behavioral factors may significantly influence these patterns, underscoring the need for integrated health and nutrition interventions that target maternal and early childhood support.